Platelet and von Willebrand factor interactions at the vessel wall - Ruggeri, Z. M. (Hämostaseologie, 2004)
The process of platelet thrombus formation contributes to the haemostatic response that prevents excessive blood loss after tissue injury, but may become a life-threatening disease mechanism by causing the acute thrombotic occlusion of atherosclerotic arteries. The participation of platelets in the formation of thrombi is centered on their adhesive properties and the ability to respond to stimuli with rapid activation. Platelet adhesion and activation are multifaceted and modulated by different environmental conditions, suggesting that it should be possible to obtain a selective pharmacological inhibition of the pathways more relevant to atherothrombosis than to haemostasis. In particular, progress in understanding the structure and function of von Willebrand factor and the mechanisms that underlie its interactions with vascular surfaces and platelets can elucidate important differentiating aspects of normal haemostasis and pathological arterial thrombosis.
Keywords: Platelet; adhesion; aggregation; von Willebrand factor; thrombosis